HADITH-BASED TARGHIB AND TARHIB AS MOTIVATION STRATEGIES IN IMAM AL-MUNDHIRI’S DIDACTIC WORK - Nelmi Hayati Nelmi; Nur Hamidah Pulungan; Fuji Pratami; Edriagus Saputra; Muhajirah Binti Jamaluddin (Journal International Inspire Education Technology, 2025)
This study explores the concepts of targhib (motivation through promises and hope) and tarhib (motivation through warnings and threats) as reflected in Imam al-Mundhiri’s didactic work Al-Targhib wal-Tarhib, which compiles Prophetic hadiths on encouragement and deterrence. Using a qualitative descriptive approach through library research, this study analyzes selected hadiths thematically to identify their educational and psychological implications. The findings reveal that the targhib–tarhib framework represents a balanced motivational system in Islamic education, combining positive reinforcement with moral awareness and behavioral control. Imam al-Mundhiri’s work demonstrates how the Prophet Muhammad (peace be upon him) utilized emotional and spiritual stimuli to nurture faith, discipline, and ethical conduct among learners. In the perspective of educational psychology, this method aligns with reinforcement and behavior modification theories but extends beyond them by integrating spiritual and moral dimensions. The implementation of targhib–tarhib principles in contemporary learning environments can serve as an effective strategy to enhance students’ intrinsic motivation, character formation, and emotional intelligence, contributing to the development of holistic and value-based education.